Algorithm-based troubleshooting to manage bleeding during thoracoscopic anatomic pulmonary resection - Igai, Hitoshi (J Thorac Dis, 2019)
BACKGROUND: Few studies have reported on the effects of intraoperative complications, such as vessel injury, during thoracoscopic anatomic pulmonary resection. We evaluated intraoperative vessel injury and assessed troubleshooting methods for thoracoscopic anatomic pulmonary resection. METHODS: A total of 378 patients underwent thoracoscopic anatomic pulmonary resection between April 2012 and March 2018, 40 of whom were identified as having an intraoperative vessel injury. In our department, we treat significant bleeding based on the algorithm shown in Figure 1. We analyzed the injured vessels and hemostatic procedures employed and compared perioperative outcomes in patients with (n=40) or without (n=338) a vessel injury. Additionally, we examined the data on a year-by-year basis from April 2012, and perioperative results were compared in each year. RESULTS: The vessel injured was a branch of the pulmonary artery in 22 cases (55%). Hemostasis was achieved by applying a thrombostatic sealant in 26 cases (65%). Although patients without a vessel injury had a shorter operation time, less intraoperative blood loss, and shorter duration of chest tube drainage, no significant differences in the length of postoperative hospitalization or morbidity were observed. The occurrence rate of significant intraoperative bleeding in the last year measured was similar to that in the first year measured. CONCLUSIONS: Thoracoscopic anatomic pulmonary resection is feasible and safe if the surgeon performs appropriate hemostasis, although vascular hazards might be inherent during thoracoscopic anatomic pulmonary resection, regardless of the surgeon’s experience.